2013
DOI: 10.13181/mji.v22i4.602
|View full text |Cite
|
Sign up to set email alerts
|

The different pattern of blood S100B protein and GFAP concentrations in ischemic stroke

Abstract: AbstrakLatar belakang: Terdapat kaitan antara stroke dengan protein S100B dan glial fibrillary acidic protein (GFAP) yang terlepas saat iskemia. (OR = 3,9; p < 0,001) . Nilai median kadar GFAP didapatkan lebih tinggi bermakna pada subyek yang masuk dengan NIHSS berat (nilai median 0,374 ng/mL) daripada yang masuk dengan NIHSS ringan (nilai median 0,047 ng/mL) dan sedang (nilai median 0,043 ng/mL) (p < 0,05). Kesimpulan: Kadar protein S100B semakin tinggi bermakna seiring dengan semakin beratnya NIHSS, sedang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The more extended the damage, the higher the elevation of serum GFAP. The higher concentration is commonly seen in intracerebral haemorrhage rather than ischemic stroke [9]. In this study, we sought to understand the pathomechanism of brain injury in acute stroke by analysing GFAP – a product of astrocyte and looking into stroke severity after 1 month of onset.…”
Section: Discussionmentioning
confidence: 99%
“…The more extended the damage, the higher the elevation of serum GFAP. The higher concentration is commonly seen in intracerebral haemorrhage rather than ischemic stroke [9]. In this study, we sought to understand the pathomechanism of brain injury in acute stroke by analysing GFAP – a product of astrocyte and looking into stroke severity after 1 month of onset.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the ability of animals to recover from CNS injuries or degenerative diseases depends on the deficiency or excess availability of MT-I/-II [7][8][9][10][11]. MT has equally been demonstrated to be down-regulated in cases of induced intoxication [12] and infection [13] but its correlated effect to other astrocyte proteins has yet to be tested.GFAP is expressed in mature astrocytes in the CNS [14]. It is a member of the family of cytoskeletal proteins and is the primary intermediate filament with a size of 8-9 nm, highly specific to the CNS.…”
mentioning
confidence: 99%
“…GFAP is expressed in mature astrocytes in the CNS [14]. It is a member of the family of cytoskeletal proteins and is the primary intermediate filament with a size of 8-9 nm, highly specific to the CNS.…”
mentioning
confidence: 99%